Unilesional mycosis fungoides is associated with increased expression of microRNA‐17 92 and T helper 1 skewing. (1st May 2019) - Moyal, L.; Gorovitz‐Haris, B.; Yehezkel, S.; Jacob‐Hirsch, J.; Bershtein, V.; Barzilai, A.; Rotem, C.; Sherman, S.; Amitay‐Laish, I.; Feinmesser, M.; Hodak, E.
Summary: Background: The molecular basis of unilesional mycosis fungoides (MF), characterized by a solitary lesion that is clinicopathologically indistinguishable from multifocal patch or plaque MF (early MF), is unknown. Objectives: To investigate the microRNA profile in unilesional MF distinguishing it from early MF. Methods: Biopsy samples of unilesional MF and early MF were evaluated with the Affymetrix microRNA array, with further comparison with inflammatory dermatosis, using quantitative polymerase chain reaction. NanoString technology was applied to analyse the gene expression of T helper (Th)1 immune markers, and immunohistochemistry was used to evaluate CXCR3 and GATA‐binding protein 3 (GATA3) markers for Th1 and Th2 cells, respectively. Results: Unilesional MF had a significantly higher level of expression of all members of the microRNA miR‐17 92 cluster than early MF. Specifically, unilesional MF had a higher miR‐17 level than early MF and inflammatory dermatoses. There was downregulation of the expression of phosphatase and tensin homolog (PTEN) and CREB1, known targets of miR‐17 92 members; higher gene expression of interleukin‐2 and interferon‐γ; and a statistically lower average percentage of GATA3 + dermal cells (6·7% vs. 42·3%), were detected in unilesional MF compared with early MF. High immunoreactivity of CXCR3 was noted in both unilesional and early MF. Conclusions: Unilesional MF exhibits a microRNA profile distinct from that of conventional early MF, with a higher level of miR‐17 92 members along with Th1 skewing. These findings suggest a robust reactive T‐cell immune response in unilesional MF and might account for the localized nature of this disease.